Diffusion-weighted Imaging Shows Cytotoxic and Vasogenic Edema in Eclampsia - Koch, Sebastian; Rabinstein, Alejandro; Falcone, Steven; Forteza, Alejandro (American Journal of Neuroradiology, 2001)
Summary: In eclampsia, MR imaging shows reversible T2 hyperintensities in a parietal and occipital distribution. Findings on diffusion-weighted images suggest that these abnormalities are areas of vasogenic edema. We describe the presence of both cytotoxic and vasogenic edema, as detected by diffusion-weighted imaging, in a woman with eclampsia. Follow-up MR imaging showed that the regions of cytotoxic edema progressed to cerebral infarction. This case suggests that diffusion-weighted imaging allows the early detection of ischemic infarcts in patients with eclampsia.